(NmONOPOLI (B:s (NtOPOLOGI^ESKIE I WARIACIONNYE METODY (B: (NsBORNIK STATEJ (B: (NpEREWOD S ANGLIJSKOGO (B/s - (NmONASTYRSKIJ(B, (NmIHAIL iLXI^s; (NsERGEEW(B, (Na(B.(Ng(B.s; (NmONASTYRSKIJ(B, (NmIHAIL iLXI^s; (NsERGEEW(B, (Na(B.(Ng(B.s ((NmOSKWA (B:s (NmIR (B,s, 1989)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NmATEMATI^ESKIE ISSLEDOWANIQs